NO ASSOCIATION BETWEEN CALPROTECTIN (S100A8) SUBUNIT GENE POLYMORPHISM AND PATIENTS WITH CHRONIC AND AGGRESSIVE PERIODONTITIS IN DRAVIDIAN POPULATION - SAMBHAVI BHAGAVATHEESWARAN; VINU RAMACHANDRAN; JEFFY RAJAN SOUNDARA RAJAN; SAMBANTHAM SHANMUGAM; KARTHIKEYAN GURUMOORTHY; ANANDAN BALAKRISHNAN (International Journal of Pharma and Bio Sciences, 2016)
Calprotectin is an inflammatory regulator whose elevated levels are implicated in periodontitis. S100A8 subunit of calprotectin has pro-inflammatory activity. The present study aims to determine the association of single nucleotide polymorphism (SNP) in the calprotectin subunit gene (S100A8) in participants from Dravidian ethnicity. The study included 236 individuals in total, of which 60 were patients with chronic periodontitis (CP), 50 were cases with aggressive periodontitis (AgP) and 126 were healthy controls. Genomic DNA was extracted from the white blood cells and the SNP rs3795391 (A→G) of calprotectin gene S100A8 was screened by allele-specific polymerase chain reaction (AS-PCR). Our study showed lack of association of rs3795391 with chronic periodontitis and aggressive periodontitis (p=0.5764; >0.05). Thus rs3795391 SNP may not contribute to susceptibility of periodontitis in the patients of Dravidian ethnicity. Further study on a larger population is essential to understand the allelic significance of this SNP.